Fuzzy Logic Control of an Automatic Changeover for the Management of a Grid-Connected Photovoltaic System - Abraham Dandoussou; Pierre Kenfack (International Transactions on Electrical Energy Systems)
The main objective is to design a smart switch controlled using fuzzy logic which is able to take decisions on different sources of energy in a very brief “switching time” to avoid load shedding. For that, a fuzzy controller is implemented by considering input signals from three power sources: photovoltaic array, batteries, and grid. The inputs are irradiance being the instantaneous measurement of solar energy, voltage range for the power grid, and state of charge for the battery to be able to know if the battery can supply or not. For these corresponding inputs, Takagi’s fuzzy inference system was applied, that permitted to have linear constants as outputs. as such as to be able to control the switch with respect to the source available at a particular period of the day, either day or night. Designing the fuzzy logic controller was able to take decisions with respect to the conditions. The load feeding signal behaviour has been obtained when either of the switches are open or closed over a period of 1000 s. In this system, the batteries charge is either done by the PV array or the power grid according to the established rules of the system.